Metabonomics and physiology revealed the critical function of 5-Phosphoribosylamine and antioxidant enzymes in enhancing aged oat seed germination - Yi Hua; Linling Dong; Shengnan Sun; Kexin Wang; Yilin Zou; Yongqi Gao; Ting Gong; Guofu Hu; Ligang Qin (BMC Plant Biology)
Abstract Effective Microorganism (EM) is widely employed as a growth promoter in agricultural practices. The aging of oat seeds not only directly impairs agricultural production but also exerts adverse effects on biodiversity. The mechanism through which EM influence the germination of aging seeds remains unclear. In this experiment, the EM bacterial solution underwent pretreatment, which included the original-solution treatment (OrT), supernatant treatment (SuT), and sterile treatment (StT). Aging of oat seeds was induced using the pretreated EM bacterial solution. In this study, the EM bacterial solution facilitated the enhancement of the germination rate, germination index, and vitality index of aged seeds, with SuT demonstrating the most pronounced effects. Specifically, SuT resulted in a significant increase in APX and POD activities, while significantly reducing the malondialdehyde content. In addition, metabolic profiling highlighted the significance of 5-phosphoribosylamine in the purine metabolic pathway. Particularly in the SuT, the upregulation of 5-phosphoribosylamine facilitated the synthesis of (R)-Allantoin, consequently augmenting antioxidant enzyme activity.